Investigating the Fuel Cell Performance Tradeoffs of Thick Catalyst Layers - Rifael Z. Snitkoff‐Sol; Yan Presman; Lior Elbaz (ChemElectroChem)
Platinum group metal‐free (PGM‐free) catalysts are showing increasing performance and durability and are considered as viable candidates for replacing precious metal‐based catalysts for the oxygen reduction reaction (ORR) in fuel cells. Due to the low intrinsic activity and low active site density, large quantities of the PGM‐free catalysts are needed to obtain high performance. Consequently, the resulting high catalyst loadings induce several interesting and opposing phenomena, namely, lower ORR kinetic losses due to an increase in the number of active sites and much higher mass and charge transport losses. In this work, Fourier‐transformed alternating current voltammetry (FTacV) and electrochemical impedance spectroscopy (EIS) measurements are employed to systematically deconvolute the gains and losses to the activity due to the high loading of PGM‐free catalysts and relate the underlying processes to the observed fuel cell performance. EIS is analyzed via extraction of the distribution of relaxation times, obtaining a model‐free analysis of the physical processes in the cell. Combined with FTacV measurements, the obtained catalyst loading optimum from a mechanistic point of view is explained. The combined use of advanced alternating current techniques for the analysis of operating fuel cells is an important step toward the rational design of the catalyst layer.